Tarbiyah Jinsiyah ‘Ulwan dan Tazkiyatun Nafs al-Ghazali: Solusi Adab Pergaulan Remaja di Era Digital - Najma Zahiroh; Ahmad Barizi (Lembaga Yasin AlSys, 2026)
Although adolescent social conduct and sexuality education have received attention in various studies, research specifically integrating tarbiyah jinsiyah from Abdullah Nashih ‘Ulwan’s perspective and tazkiyatun nafs from Imam Al-Ghazali’s perspective remains limited. This study aimed to integrate the concept of tarbiyah jinsiyah with the values of tazkiyatun nafs as a conceptual solution for developing ideal adolescent social conduct in the digital era. The study employed a qualitative approach with a literature review design. The data sources comprised reputable scholarly literature selected according to inclusion and exclusion criteria through searches of Google Scholar and SINTA. The data were analyzed using the Miles, Huberman, and Saldaña model through the stages of data condensation, data display, and conclusion drawing. The results showed that integrating the two concepts produced three main pillars of adolescent social conduct. First, the internalization of haya’ as a foundation for maintaining the boundaries of awrah and bodily privacy on social media. Second, the actualization of ‘iffah through digital self-regulation in guarding one’s gaze against exposure to erotic visual content. Third, the cultivation of muraqabah as an awareness that individuals are constantly under the supervision of Allah the Almighty, thereby strengthening adolescents’ gender identity amid the challenges of identity crises. These findings contribute to the development of Islamic education that integrates jurisprudential and Sufi perspectives and expands understanding of Islamic sexuality education based on internal self-control. This study emphasizes the importance of strengthening the values of haya’, ‘iffah, and muraqabah in safeguarding adolescents’ morality and social conduct in the digital era. Practically, this integrative model can provide a foundation for parents, educators, and educational institutions in developing parenting and habituation practices based on Sufi values. Future research should empirically examine the effectiveness and implementation of this model within families and educational institutions.